Synthetic aperture imagery for high-resolution imaging sonar - Huang, Pan; Yang, Peixuan (Frontiers in Marine Science, 2022)
Synthetic aperture sonar (SAS) can provide high-resolution underwater image to users. Traditional fast imaging algorithms designed for multiple-receiver synthetic aperture sonar (MSAS) are very complicated, as the deducing of point target reference spectrum (PTRS) and development of imaging algorithm are very complicated. To solve this issue, this paper proposes an imaging algorithm for MSAS system. The presented method firstly approximate the two-round slant range based on phase centre approximation method. The PTRS including quasi-monostatic term and bistatic deformation term can be easily deduced. After compensating the bistatic deformation term based on the interpolation and complex multiplication with the preprocessing step, the MSAS imagery can be simplified to the focusing of traditional monostatic synthetic aperture sonar. That is to say, conventional imaging algorithms designed for traditional monostatic synthetic aperture sonar can be directly used. The presented method providing high-resolution imaging results is easily conducted compared to traditional methods.